(NbIBLIOTEKA (B"(NoGONEK(B". (NoTE^ESTWENNAQ KLASSIKA (B/ s - (NkRYLOW(B, (Ni(B.(Na(B.s ((NmOSKWA(B: s (NpRAWDA(B, s, 1984)
(NsOBRANIE SO^INENIJ RUSSKOGO KLASSIKA iWANA kRYLOWA(B.s
rus
Keywords: (NsATIRA(B, (N@MORs; (NpOWESTX(B, (NRASSKAZYs; (NsTIHOTWORENIQs; (NpROZAs -- (NbASNIs -- (NpXESYs